Spices from the wild - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Prices of cloves, cardamom, ginger, vanilla and black pepper have fallen by up to 75% because of over-production. As a result, the current unfavourable prices for these well-known spices are a disappointment for all producers and a near disaster for...